Synthesis and Characterization of Corn Starch Crosslinked with Oxidized Sucrose. (30th November 2018) - Wang, Pengkai; Sheng, Feng; Tang, Shang Wen; ud‐Din, Zia; Chen, Lei; Nawaz, Asad; Hu, Chun; Xiong, Hanguo
Abstract : In this study, oxidized sucrose is employed to crosslink corn starch at 100, 110, and 120 °C. The cross‐linked starch is analyzed by Fourier transform infrared (FTIR) and 1 H nuclear magnetic resonance ( 1 H NMR) spectroscopy. The X‐ray diffraction (XRD) analysis reveals that cross‐linked starch exhibits a "V" crystal structure after modification. Thermogravimetric (TG) analysis demonstrates that the destruction of the crystal structure increases the thermoplasticity of the starch. A decrease in the viscosity of the cross‐linked starch using a Rapid Visco Analyzer (RVA) is noted. However, compared with native starch, the swelling power of cross‐linked starch shows a negative correlation with treatment temperature. Furthermore, the cross‐linked starch that is treated at 100 °C experiences a fivefold increase in both swelling ratio and water binding capacity, compared with native starch. Additionally, low‐field nuclear magnetic resonance (low‐field NMR) analysis verifies the excellent hydrophilic properties of the cross‐linked starch. The oxidized sucrose‐modified starch (OSMS) is an alternative for improving starch‐based products, potentially in turn guiding further advancements in the pharmaceutical and food industries. Abstract : Oxidized sucrose is employed to crosslink corn starch at 100 °C, 110 °C, and 120 °C. Furthermore, the structural characterisation, physicochemical, and thermal properties of cross‐linked starch are determined. The oxidized sucrose exhibits superior characteristics in improving of hydrophilic properties of starch, which can be an alternative for improving starch‐based products, potentially in the pharmaceutical and food industries.